Financial and Social Well-being Performance after Privatisation of the Port of Brisbane: A Case Study - Mudiyanselage Upali Ranjith Jayasundara; Greg Jones; John Sands (Australasian Accounting, Business and Finance Journal, 2020)
Available literature has failed to provided a satisfactory expalination to the contradiction between ‘the theory of the firm’ and ‘stakeholder theory’ predictions related to financial and socialwellbeing performance of public versus private firms. Limited literature has evaluated the financial and social-wellbeing performance of privatised ports in Australia. This study investigates the potential impact of the privatisation of the Port of Brisbane Corporation (PBC) to the Port of Brisbane Proprietary Limited (PBPL) on its financial and social-wellbeing performance. Mixed methods research is employed following the theory of the firm, investigating the relationship between the change of ownership and financial and social-wellbeing performance of PBPL, under pre-and post-privatisation conditions. Firstly, quantitative methods are used to analyse secondary data from annual financial reports, comparing ratios between 2005 and 2017. Privatisation occurred during 2011 and this year was eliminated from the study as both ownership types existed. MANOVA will be used 'before and after privatisation' to test the null hypothesis, and subsequentially to design open-ended questions for interviews of PBPL employees. MANOVA results did not support the null hypothesis, consequently, ANOVA and Tukey's posthoc tests were conducted, provideding significant differences, with improved performance under privatisation. Findings from interviews provided explainations related to improvments the financial and social-wellbeing performance during private (2012-2017) compared to State ownership (2005-2010). This study revealed private ownership, as posited by the theory of the firm, maximised profits, and following stakeholder theory predictions managed social well-being.
Keywords: privatisation; privatization; Australia; financial performance; social well-being performance